Pengaruh Kesadaran Wajib Pajak, Pemahaman Wajib Pajak Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Sahwa Nadia Fitri; Annisa Annisa (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
This study aims to explain the influence of taxpayer awareness, understanding of taxpayers and tax sanctions on individual taxpayer compliance is the aim of this research. Determination of the sample using incidental sampling method. The population in this study were all individual taxpayers registered at the Padang Satu Pratama Tax Office and the sample used in this study was 100 respondents. The data analysis technique in this study was multiple linear regression analysis with the SPSS program. The results of this study can be concluded that taxpayer awareness, understanding of taxpayers and tax sanctions have a positive effect on taxpayer compliance.